Joyride - Reynolds, Emer; Keogan, Ailbhe; O'Sullivan, Aoife; Lynch, Tristan Orpen; Colman, Olivia; Reid, Charlie; O Mearain, Lochlann, 1973-; Ingenious Media; Fis Eireann/Screen Ireland (Firm); Embankment Films; Subotica Entertainment (Firm); Magnolia Home Entertainment (Firm) (Los Angeles, CA Magnolia Home Entertainment, 2023)
A headstrong solicitor's plan to offload her new born baby to a friend, is derailed when a vulnerable but opinionated teenager steals their taxi.
Originally released as a motion picture in 2022.
Wide screen (2.39:1).
Special feature: Making of Joyride.
Director of photography, James Mather ; editor, Tony Cranstoun ; music, Ray Harman.
Olivia Colman, Charlie Reid, Lochlann O Mearain.
Rating: Not rated.
Keywords: Infants -- Drama; Boys -- Drama; Interpersonal relations -- Drama; Theft -- Drama; Ireland -- Drama; Comedy films; Drama; Feature films; Fiction films; Road films; Video recordings for the hearing impaired